2018
DOI: 10.1155/2018/1463579
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivities of Traditional Medicinal Plants in Alexandria

Abstract: In traditional folklore, medicinal herbs play a vital role in the prevention and treatment of microbial diseases. In the present study, the phenolic profiles of the medicinal plants Asparagus aethiopicus L., Citrullus colocynthis L., Senna alexandrina L., Kalanchoe delagoensis L., Gasteria pillansii L., Cymbopogon citratus, Brassica juncea, and Curcuma longa L. were determined by high-performance liquid chromatography with a diode-array detector method. The results revealed rich sources of important compounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 53 publications
(61 reference statements)
2
54
0
Order By: Relevance
“…M. rhodantha was the best source of antioxidants in this study because it was rich in the strong antioxidants of gentisic acid, chlorogenic acid, caffeic acid, and protocatechoic acid. The four of these phenols have been associated with anti-oxidant activities as revealed in several studies [17,38,39]. Previous reports have found that gentisic acid provided protection to human erythrocytes against gamma radiation [25].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…M. rhodantha was the best source of antioxidants in this study because it was rich in the strong antioxidants of gentisic acid, chlorogenic acid, caffeic acid, and protocatechoic acid. The four of these phenols have been associated with anti-oxidant activities as revealed in several studies [17,38,39]. Previous reports have found that gentisic acid provided protection to human erythrocytes against gamma radiation [25].…”
Section: Discussionmentioning
confidence: 94%
“…Chlorogenic acid is the ester of caffeic acid and is much more common than gentisic acid. Chlorogenic acid was isolated from different plants species such as Etlingera elatior leaves, coffee, and fruit [27] as well as medicinal plants [17]. The chlorogenic acid is known for strong its anti-oxidant, anti-cancer, anti-inflammatory, and antiviral properties, and modulates the anti-oxidant enzyme activities [28,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plants have been used in traditional medicine to treat numerous diseases and pathological conditions. Certain bioactive compounds present in plants have been widely researched and have been shown to be antioxidant, anticarcinogenic and anti‐inflammatory agents . Baicalin has been reported to attenuate TNBS‐induced colitis, and water extract of taheebo also could prevent DSS‐induced colitis .…”
Section: Introductionmentioning
confidence: 99%
“…Certain bioactive compounds present in plants have been widely researched and have been shown to be antioxidant, anticarcinogenic and antiinflammatory agents. [3][4][5][6][7] Baicalin has been reported to attenuate TNBS-induced colitis, and water extract of taheebo also could prevent DSS-induced colitis. [8,9] These bioactive compounds provide an alternative chance for the treatment of colitis.…”
Section: Introductionmentioning
confidence: 99%